2023
DOI: 10.1080/15248372.2023.2172414
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Executive Functions in Mathematical Cognition

Abstract: These perspectives have implications for research in mathematical cognition. We tackle the problem that although individuals clearly exercise inhibitory control in mathematical contexts, researchers find that the relations between inhibitory control and mathematics are sometimes "weaker than expected" (Lee & Lee, 2019, p. 29). In this review, we identify how children and adults use inhibitory control in specific foundational symbolic and non-symbolic mathematical contexts, with attention to concepts learned in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…This involves complex issues of how humans acquire, process, and apply mathematical knowledge (Moustafa et al, 2017). In education, exploring the processes and mechanisms of mathematical cognition helps optimize teaching methods, improve students' learning processes, and enhance overall teaching effectiveness (Gilmore, 2023;Medrano and Prather, 2023). Simultaneously, in neuroscience, studying the neural basis of mathematical cognition allows us to understand the operating mechanisms of the brain more deeply (Matejko and Ansari, 2015;Looi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This involves complex issues of how humans acquire, process, and apply mathematical knowledge (Moustafa et al, 2017). In education, exploring the processes and mechanisms of mathematical cognition helps optimize teaching methods, improve students' learning processes, and enhance overall teaching effectiveness (Gilmore, 2023;Medrano and Prather, 2023). Simultaneously, in neuroscience, studying the neural basis of mathematical cognition allows us to understand the operating mechanisms of the brain more deeply (Matejko and Ansari, 2015;Looi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest this is not likely to be effective. On the other hand, teaching specific knowledge and skills that could support using EF in classroom contexts may be effective (Medrano & Prather, 2023;Niebaum & Munakata, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Executive functions play a critical role in mathematical achievement (Bull & Lee, 2014;Cragg et al, 2017). Slowly, research has started to move from examining broad relations between these cognitive capacities and general math skills to studying specific contributions to particular math abilities or math knowledge (Coulanges et al, 2021;Fuhs et al, 2021;Lee & Lee, 2019;Medrano & Prather, 2023;Van Dooren & Inglis, 2015;Wilkey, 2023). From the three core executive functions (Diamond, 2013;Miyake et al, 2000), inhibitory control has been posed as a pivotal skill to suppress misleading information in both science and mathematics (Brookman-Byrne et al, 2018;Vosniadou et al, 2018).…”
Section: Contributions Of Executive Functioning To Fraction Knowledgementioning
confidence: 99%
“…Using G*Power (Faul et al, 2009), we performed an a priori power analysis to determine the sample size required to detect effect sizes akin to those reported in correlational studies of mathematical achievement and executive functions, r ~ .30 (Medrano & Prather, 2023;Pascual et al, 2019). Such analysis indicated that 80 participants were sufficient to detect medium to large effect sizes (r > .30) with 80% power and alpha = 0.05.…”
Section: Participantsmentioning
confidence: 99%